2019
DOI: 10.1097/cej.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sleep habits and the risk of breast cancer among Chinese women: a case–control study

Abstract: Previous observational studies have inconsistently suggested that poor sleep is a novel risk factor for breast cancer (BC). However, these studies mainly focused on sleep duration; other sleep domains were rarely reported. The aim of this study was to evaluate the association of a broad range of sleep domains with the risk of BC incidence. We used a community-based 1 : 1 individual matched case-control design that included 401 female patients with incident BC and 401 age-matched and area-matched female control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The identification of risk factors and susceptible populations of breast cancer has become imperative in China given the recent marked increase of breast cancer cases among Chinese women 1,2 . Epidemiological studies identified cigarette smoking, alcohol consumption, and sleep disorders among the several environmental risk factors for breast cancer 3–5 . Nevertheless, only a small proportion of exposed people develop breast cancer, suggesting that breast cancer incidence is not only correlated with environmental factors, but also with genetic susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of risk factors and susceptible populations of breast cancer has become imperative in China given the recent marked increase of breast cancer cases among Chinese women 1,2 . Epidemiological studies identified cigarette smoking, alcohol consumption, and sleep disorders among the several environmental risk factors for breast cancer 3–5 . Nevertheless, only a small proportion of exposed people develop breast cancer, suggesting that breast cancer incidence is not only correlated with environmental factors, but also with genetic susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents characteristics of the 17 included studies, three with case-cohort design [ 40 42 ], six cohort [ 23 25 , 43 45 ], and eight case–control [ 46 53 ]. The studies were published during 2001–2021, mainly in North America (N = 10), followed by Europe (N = 3), Israel (N = 2), Australia (N = 1), and China (N = 1).…”
Section: Resultsmentioning
confidence: 99%
“…This investigation also showed that sleep quality, well-known to be influenced by occupational features ( 42 ), is also linked to the state of menopause. However, no association was found between BC risk and sleep duration, sleep quality, use of sleep medication, frequency of insomnia and daytime napping in a case-controlled study conducted in China ( 65 ). This research showed that night shift work and frequency of nocturnal awakenings were associated with an increased risk of BC independently from menopausal status and tumour estrogen receptor status.…”
Section: Mechanistic Pathwaysmentioning
confidence: 98%
“…However, even with regard to this proposed mechanism, the studies have shown contested results; a case-controlled study performed in Vancouver found no association between nocturnal artificial light and BC ( 64 ); whereas a case-controlled study performed in China ( 65 ) and a population-based case-controlled study in Spain ( 66 ) both showed that there was an increased risk of BC associated with exposure to night light, in particular, with external light in the blue spectrum.…”
Section: Mechanistic Pathwaysmentioning
confidence: 99%